17.1k views
1 vote
9x -3y=3
3x+8y=-17 elimination

User Kbang
by
6.1k points

1 Answer

1 vote
Multiply the second equation by -3, then add the equations together.(9x3y=3)−3(3x+8y=−17)Becomes:9x3y=39x24y=51Add these equations to eliminate x:27y=54Then solve27y=54for y:27y−27=54−27(Divide both sides by -27)y=−2Now that we've found y let's plug it back in to solve for x.Write down an original equation:9x3y=3Substitute−2foryin9x3y=3:9x(3)(−2)=39x+6=3(Simplify both sides of the equation)9x+6+−6=3+−6(Add -6 to both sides)9x=−39x9=−39(Divide both sides by 9)x=−13Answer:x=−13 and y=2

Np
User DACW
by
5.1k points